TWO-DIMENSIONAL INTERPOLATION OF POTENTIAL GEOPHYSICS DATA - Sasongko Hadipandoyo (Scientific Contributions Oil and Gas, 1992)
Many types of geophysical survey involve making numerical observations as a large number of localities in a so called survey area. In order to display the result of such a survey in a way which can be easily assimilated by the interpreter they must be process a map form with the X and Y values (geographical position) associated with each data point.